Educational Prospects Of Nanoscience And Nanotechnologies For Enhancing Students’ Scientific Literacy - Xaydarov Boymurod Abduqodir o‘g‘li (Genius Journals, 2025)
Nanoscience and nanotechnologies (NNT) occupy a central place in the scientific and technological progress of the 21st century. They deal with the study and manipulation of matter at the nanometer scale, where unique physical, chemical, and biological properties emerge. Along with their rapid development, nanotechnologies are gaining increasing importance in education, as they directly contribute to the enhancement of scientific and technological literacy (STL).
Keywords: Nanoscience; nanotechnologies; education; scientific literacy